(untitled) (Bioagro, 2025)
This study analyzed the rhizosphere bacterial communities in sugarcane fields subjected to different durations of agronomic management: recent (5 years) and long-term (over 50 years). The objective was to evaluate the diversity of rhizosphere bacteria using 16S rRNA gene sequencing and assess their correlation with soil management practices. Results showed distinct bacterial compositions between recently and long-term managed fields. Significant associations were observed between bacterial species and soil conditions characterized by high electrical conductivity (EC), elevated concentrations of Ca²⁺, K⁺, Fe²⁺/Fe³⁺, and Mg²⁺, and low CO₃²⁻ levels. Dominant species included Bacillus megaterium, Bacillus subtilis, and Bacillus simplex, representing the phyla Actinobacteria, Proteobacteria, and Firmicutes, respectively. An analysis of the outlying mean index explained 76.2 % of the total variation, highlighting key soil factors. The first axis (44.7 %) correlated with EC and organic matter content (OM), while the second axis (31.5 %) was associated with extractable phosphorus (P) and potassium (K) levels. These findings underscore the influence of soil physicochemical properties-such as EC, OM, and nutrient availability-on rhizosphere bacterial diversity and composition. These variables modify the soil microenvironment, favoring certain bacterial groups over others and directly impacting soil fertility and agricultural productivity. This study provides insights into the interaction between rhizosphere bacteria and soil management practices. Understanding microbial dynamics in long-term managed systems paves the way for strategies that improve soil health and crop productivity in intensive agricultural systems.